OPTIMIZATION OF THE LOGISTICS PROCESS IN CARGO TRANSPORTATION (International Conference on Economics, Finance, Banking and Management, 2025)
The article deals with the introduction of modern methods of transport logistics, the possibility of road transport by rail, as well as the effectiveness of modern logistics processes in Uzbekistan.